Pericles' character in Old Attic comedy - O.A. Rykantsova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper discusses Aristophanes’ plays and the surviving fragments of other Old Attic comedy authors as one of the most important sources on Pericles’ biography. The main themes of comic invectives at Pericles were analyzed. Besides the caricature of Pericles’ appearance, the comedies contain serious attacks against the politician: Pericles’ omnipotence and the tyrannical nature of his power are demonstrated; the politician is accused of unleashing the Peloponnesian War and its incorrect conduct. Such problems as the distortion degree of Pericles’ comic character, its perception by the Athenian public, and the influence of comedy on the historical tradition concerning Pericles’ politics remain debatable and do not lose their relevance. The paper is another attempt to correlate Pericles’ image in comedy with what we know about him from other sources. Despite the subjectivity of the comic genre, comedy allows us to imagine more vividly Pericles’ character reflected in the writings of historians, in “The History” by Thucydides in particular. Perhaps, the attacks on Pericles in comedies were not taken seriously by the public while the strategist’s authority was unshakable, but at the beginning of the Peloponnesian War the comic accusations could intensify enmity to the disgraced politician. The word of fiction, especially when aptly said, has a great influence on historical tradition, an example of which is Pericles’ biography written five centuries after his death by Plutarch, who actively used the fragments of Old Attic comedy in his works.